SELEKSI INDUK KAMBING PERANAKAN ETAWAH BERDASARKAN NILAI INDEKS PRODUKTIVTAS INDUKPADA BOBOT SAPIH DI DESA DADAPAN KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Noviar Kusuma Negara; Idalina Harris; Novirzal . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
Doe productivity index (DPI) on wean weight refers to doe capability to wean kid in specificweight per year. So it’s parameter could be used as selection tool to find the best doe as maternalresource. On that purpose, record of 30 PE doe in Dadapan Village, Sumberejo SubdistrictTanggamus Municipal, Lampung Province, were evaluated to determine doe productivity index.Evaluation were done in October-November 2013, which are included data ; Doe age. Kid bornweight, Type of offcpring, and corrected weaning weight. Parameters involved are: average weanweight (AWW), most probable producing ability (MPPA), reproduction efficiency (RE), and doeproductivity index (DPI), respectively.Data calculation show that AWW (kg), MPPA (kg), RE (%), and DPI (kg) are: 22,75±1,94 kg;22,75±0,15 kg; 94,78±8,80%, and 21,56±1,97 kg, respectively. On the other side, the best five DPIwere resulted by doe Q1 (26,66 kg), H1 (26,52 kg), O2 (24,23 kg), J1 (24,06 kg), and A1 (24,03kg). Based on the result, it concluded that those five doe could be used as main maternal resources inDadapan Village, Sumberejo Subdistrict Tanggamus Municipal, Lampung Province.